Pollutant removal through phytoremediation: a review - Singh, Rajeev Pratap; Abdeljawad, Nour Salah (Environmental and Toxicology Management, 2024)
Pollution is a serious problem faced by Indonesia, where many water sources are contaminated by domestic, industrial and agricultural waste. These sources of pollution include fecal waste, household waste, and hazardous chemicals such as heavy metals and microplastics, requiring effective solutions to restore the quality of aquatic ecosystems. Several mechanisms that occur during the phytoremediation process in reducing contaminants in water include phytoextraction, phytostabilization, phytovolatilization and rhizofiltration. The success of the phytoremediation process is influenced by plant characteristics, environmental conditions, and the nature of pollutants. The level of phytoremediation efficiency in reducing pollutants can be estimated using the percentage reduction formula. Observations on plant growth such as biomass weight, root length, and plant height are needed to evaluate plant health and symptoms of phytotoxicity that may arise due to contact with contaminants on plants. Laboratory analysis of spectroscopy or chromatography is needed to determine quantitative data on the accumulation of heavy metals or other hazardous substances.